The Life and Growth of Language. Prolegomena - Whitney, William Dwight (Acta Universitatis Danubius. Communicatio, 2024)
This fragment is the Romanian translation of the first two chapters of W.D. Whitney’s 1875 most influential book, The Life and Growth of Language. Therefore, for the present article, we decided to preserve, by way of abstract, Whitney’s own words written in this regard: definition of language; man, its universal and sole possessor; variety of languages; the study of language; language learned, not inherited or made, by the individual; process of children’s learning to speak; what this involves, outside the province of the linguistic student; origin of particular words; character of a word as sign for a conception; mental training in learning language; determination of the inner form of language from without; constraint and advantage in the process; acquisition of a second language, or of more than one; learning even of native speech a never-ending process; imperfection of the word as sign; language – only the apparatus of thought.